Prevalence and SCCmec characterization of community-associated methicillin-resistant styphylooccus aureus (CA-MRSA) among young waste picker populace of the Iloilo City dumpsite - Cuadra, Marie Johanna Leopoldo
Methicillin-resistant Staphylococcus aureus is one of the most widespresd , multple drug resistant, virulent pathogen hwihc has established itself as a significant cause of hospital and community-acquiresd infection worldwide. Numerous reports have focused on the emergence of MRSA among different populations globally. Unfortunately. CA-MRSA and its associated molecular determiants among young waste pickers, who are constantly exposed to occupational and microbiological hazards have not yet been established. Colonization represents a reservoir for subsequent staphylococcal infections which is now considered to be an important public health concern due to its increasing incidence of antimicrobial resitance. This study aimed to determine the occurrence of CA-MRSA nasal colonization among the young waste picker population in a local dumpsite in Iloilo City, potential risk factor of carriage, their antibiograms, carriage of mecA gene and the SCCmec type in the isolates., Nasal carriage rates of Staphylococcus aureus and MRSA among 59 waste pickers were 80 percent (n=47) and 22 percent (n=13), repsectively. Sixty-eight percent and 11 percent of S. aureus and MRSA, respectively were determined from 44 non-waste picking subjects. Three potential risk factors were identified to be associated with nasal carriage of S. aureus among scavenging children : self reported illnesses of health-related complaints [OR 5.68 (C1 1.12, 28.80] ], the presence of skin lesions [ OR 7.37 (C1 1.31, 74.12) ] and the years of waste picking activity [ OR 8.82 (C1 1.55, 88.71) ] while high risk of MRSA carriage was found to be significantly associated with sel-reported illnesses only. Almost all MRSA and non MRSA isolates recovered from the participants were resistants to both B-lactams penicillin G (94 percent vs. 100 percent) and ampicillin (100 percent vs. 100 percent). Intermediate sensitivity to several antimicrobials namely erythromycin, clyndamycin, vancomycin, oxacillin and cefoxitin was noted to be almost similar for both subpopulations, except for vancomycin to which no intermediate sensitivity was observed among the non-waste picking group. Non-resistance to tetracycline was observed to be high (82 percent) among the S. aureus isolaates from waste pickers and should be reserved from these cases. Fifteen percent of MRSA or ( or 4 percent of the total S. aureus) from waste pcikers exhibited multiple resistances to three classes of anti-staphylococcal agents (e.g. tetraclyne, macrolide and liconsamide). Furthermore PBP2a, which mediates methicilline resistance in S. aureus, were present in 73 percent of the 15 MRSA isolates tested. Fifty-four percent of MRSA (or 13 percent of the total S. aureus) isolated from waste pickers were found to carry the mecA gene that mediates methicilline resistance in S. aureus. Moreover, among these mecA-positive MRSA, 46 percent were classified as SCCmec type IV and 7 percent was type II (13 percent and 2 percent of the total S. aureus , repectively) suggesting the spread of these pathogens in this community.